Traditional Ecological Knowledge and Community Based BiodiversityConservation in Eastern Himalayas: Learning with Monpa Tribe - Singh, Ranjay K.; Community, Monpa; Pandey, C. B. (Indian Journal of Extension Education, 2011)
The present socio-environmental research is based on conventional and participatory research observations. It demonstrates the dynamics of traditional ecological knowledge (TEK) of using paisang (Quercus griffithii) trees’ leaves in cultivation of indigenous crops under rainfed agroecosystem. Research highlights the role of community in conservation of forest species and agrobiodiversity by the Monpa community in the West Kameng district of Arunachal Pradesh, eastern Himalaya. A study area was selected purposively while respondents were selected randomly from Dinarng West Kameng district. Results indicated that for Monpa community, local cultures, traditional values and beliefs, social and ethical norms tied with local ecosystems and are the essence of their social capital. For economically poor people living in remote areas, the TEK and their strong cultural capital plays a pivotal role in conservation of paisang tree and indigenous agrobiodiversity. The indigenous agrobiodiversity are conserved under rainfed conditions and varying microecosystems for the subsistence survival. Monpa have rich and diverse socio-cultural, economic and spiritual perceptions about paisang and its related landscapes. The diverse knowledge systems about paisang trees biodiversity and location specific microecosystems significantly help in management practices pertaining to conserve the indigenous agrobiodiversity, thus help in fulfilling the food and nutritional security of Monpa. The strong cultural ethics and social capitals governed through the traditional institutions are still in vogue and valuable property of Monpa which contribute to the livelihood system and subsistence survival in rainfed ecosystem.